Zenker's diverticulum: carbon dioxide laser endoscopic surgery - Plzák, Jan; Zábrodský, Michal; Lukeš, Petr (BioMed research international, 2014)
Nowadays endoscopic diverticulotomy is the surgical approach of the first choice in treatment of Zenker's diverticulum. We report our experience with this procedure and try to sum up recent recommendations for management of surgery and postoperative care. Data of 34 patients with Zenker's diverticulum, treated by endoscopic carbon dioxide laser diverticulotomy at the Department of Otorhinolaryngology and Head and Neck Surgery, 1st Faculty of Medicine, Charles University, University Hospital Motol, Prague, Czech Republic, were prospectively stored and followed in relatively short period from May 2009 to December 2013. The average length of diverticulum was 32 mm. The average duration of surgery was 32 min. The patients were fed via feeding tube for 6.1 days and antibiotics were administered for 7 days. Mean hospitalization time was 7.4 days. We observed one transient recurrent laryngeal nerve paralysis and no other serious complications. Recurrence rate was 3%. We recommend complete transection of the diverticular septum in one procedure, systemic antibiotic treatment and exclusion of transoral intake for minimally 5 days, and contrast oesophagogram before resumption of oral intake to exclude fistula. Open diverticulectomy should be reserved for cases with inadequate endoscopic exposure and for revision surgery for multiple recurrences from endoscopic diverticulotomies.
Keywords: dospělí; Female; Adult; ženské pohlaví; Zenkerův divertikl; časové faktory; Time Factors; lidé; Aged, 80 and over; následné studie; Esophagoscopy; retrospektivní studie; prospektivní studie; Follow-Up Studies; Male; Zenker Diverticulum; Aged; Prospective Studies; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; laserová terapie; ezofágoskopie; Middle Aged; Retrospective Studies; Laser Therapy; Humans